DEVELOPING STUDENTS’ WORKSHEET USING SCIENTIFIC APPROACH IN TEACHING READING GRADE EIGHT STUDENTS OF SMP CERDAS MURNI TEMBUNG - Dwi Wulandari; Masitowarni Siregar (Universitas Negeri Medan, 2021)
This study concerns on how reading worksheet are developed for junior high school. Thisstudy was conducted by using Research and Development (R&D) design. It was started fromcollecting the data, analyzing data, designing course grid based on curriculum 2013,designing new reading worksheet, validating by experts, and revising for final product. Thenew students’ reading worksheet was designed based on scientific approach stages, which iscontained of five stages; observing, questioning, experimenting, associating, andcommunicating. The source of data of this study was the grade VIII students of SMP CerdasMurni Tembung consisting 26 students. Instrument of collecting data were questionnaire, andinterview. After analyzing data, the researcher got the students’ need in learning English. Theinterview and questionnaire result proved that the students need students’ reading worksheetwhich contains for grade VIII. The materials which were developed were focused ondescriptive text, recount text, and narrative text. The product had been validated by theexperts. The average scores are 3,8 from English subject teacher and 3,4 from Englishlecturer. It means the developing students’ reading worksheet categorized as relevant forstudents of grade VIII.